2020
DOI: 10.1016/j.asmr.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Infected Hematoma After Endoscopic Sciatic Nerve Decompression

Abstract: We present a 24-year-old male who developed an infected hematoma that resulted in sciatic nerve injury after he underwent an endoscopic sciatic nerve decompression. He underwent urgent hematoma evacuation and cultures speciated as Salmonella. At 4 months' follow-up, the patient's nerve had improved motor and sensory function. This case highlights the importance of obtaining appropriate hemostasis at the end of an endoscopic sciatic nerve decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Yoon et al described successful endoscopic resection of the tip of acetabular screw causing sciatic nerve irritation after revision total hip arthroplasty [ 10 ]. Postoperative recurrence due to the development of an infected hematoma after endoscopic sciatic neurolysis was reported in a 24-year-male that required open surgical evacuation and six weeks of postoperative antibiotics [ 8 ]. Our review analysis showed only one case of postoperative recurrence due to a foreign body reaction that was salvaged by open surgical decompression [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoon et al described successful endoscopic resection of the tip of acetabular screw causing sciatic nerve irritation after revision total hip arthroplasty [ 10 ]. Postoperative recurrence due to the development of an infected hematoma after endoscopic sciatic neurolysis was reported in a 24-year-male that required open surgical evacuation and six weeks of postoperative antibiotics [ 8 ]. Our review analysis showed only one case of postoperative recurrence due to a foreign body reaction that was salvaged by open surgical decompression [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Though piriformis syndrome was considered synonymous with DGS in the past, it has now been recognized that piriformis syndrome is only a subgroup of DGS. Other potential causes include overuse-related conditions, high-energy trauma such as acetabular fractures or posterior hip dislocations and postoperative scarring, hematoma, protruding hardware, or heterotopic ossification [8][9][10].…”
Section: Introductionmentioning
confidence: 99%